PENGEMBANGAN MEDIA GEO-SD (GEOMETRI SKETSA DIMENSI) SEBAGAI PENUNJANG KEMAMPUAN VISUAL SPASIAL - Rachmania Mirza Hariastuti; Dwi Anita; Moh. Ade Setiawan (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2018)
Every student generally has multiple intelligences with different level, one of which is visual-spatial intelligence shown by the ability to visualize an object. To acquire this kind of intelligence one can utilize media. This research, aiming at developing such a media, uses ADDIE model which is designed based on printed media which then followed by designing the electronic ones. Subjects of the research are 9 students selected by random technique. The research result electronic quiz media which can be utilized by students in interpreting 3D objects into 2D ones or vice versa.